(untitled) (Vietnam Journal of Agriculture and Environment, 2024)
Among 40 chili pepper lines that were received from the World Vegetable Center (WorldVeg), there are 36 chili pepper lines, which germinated well (4 chili pepper lines did not germinate). They were evaluated for agronomic characteristics from August 2023 to March 2024 in a plastic house and open field in Fruit and Vegetable Research Institute, Gia Lam district, Ha Noi city, Vietnam. 7 promising chili pepper lines have been identified to had high potential yield highly potential yield, nice fruit appearance, and good disease resistance, in which there are 3 lines in pendant fruit type (AVPP2001, AVPP2005, AVPP1807) and 4 lines in erect fruit type (AVPP1609-022; AVPP0506; AVPP1609085; AVPP1345). These 40 WorldVeg chili pepper lines have grown on open fields without pesticides for disease resistance evaluation from November 2023 to May 2024. The AVPP1324 line (in pendant fruit type) was highly resistant to virus disease. Ten pendant fruit lines (AVPP2005, AVPP2007, AVPP22002, AVPP9909-S, AVPP9910-S, AVPP9606-S, VI047102, AVPP0024, AVPP1342, AVPP9910, AVPP1806, AVPP1807, AVPP1324) and 7 erect fruit lines (AVPP1609-022, AVPP1609-085, VI059328, AVPP0309, AVPP1812, AVPP2076, AVPP2077) were high resistant to Stemphylium spp. disease. VI037587 line (pedant fruit) and VI044930 line (erect fruit) were resistant to Stemphylium spp. disease. Thirty-seven chili pepper lines that were highly resistant to Anthracnose disease. These WorldVeg pepper lines with good disease resistance, which are a great valuable germplasm resource for the chili pepper breeding program in Vietnam.